2003
DOI: 10.1164/rccm.200205-425oc
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Anions Induce the Maturation of Human Dendritic Cells

Abstract: Dendritic cells play a key role in immune responses. There is growing evidence that reactive oxygen species participate in signaling pathways involving nuclear factor (NF)-kappaB, leading to expression of important immune system genes. We found that, unlike H2O2, reactive oxygen species generated by the reaction of oxidase on xanthine induced early phenotypic maturation of dendritic cells by upregulating specific markers CD80, CD83, and CD86 and downregulating mannose receptor-mediated endocytosis. Maturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
69
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 31 publications
9
69
1
1
Order By: Relevance
“…5). These results indicate that ROS, as demonstrated in the activation and maturation processes [22][23][24], also play a crucial role in DC differentiation and that mitochondria are an important source of ROS in the process.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…5). These results indicate that ROS, as demonstrated in the activation and maturation processes [22][23][24], also play a crucial role in DC differentiation and that mitochondria are an important source of ROS in the process.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies showed that, whereas NADPH oxidase activation is required for DC killing of intracellular Escherichia coli, no role in DC differentiation or functions can be ascribed to NADPH oxidasederived oxygen radicals [20,21]. However, an involvement of ROS has been recently described in the activation and maturation process of DC [22][23][24].…”
mentioning
confidence: 99%
“…In DC, oxygen radicals were implicated in both DC differentiation (43) and maturation (26,27) and in IL-8/CXCL8 production (24,25). Controversial data are present in the literature about the inhibitory action (52) or the positive role (26,53) of oxygen radicals on the ability of DC to stimulate T cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Also, tobacco smoke has many toxic low molecular weight compounds that are able to directly stimulate bronchoalveolar dendritic cells (DCs). Activated DCs can discharge many of inflammatory chemokines that will induce the recruitment and activation of more DCs and other inflammatory cells such as neutrophils 13 .The pathogenic changes of lung consequenced due to its immune responsive on cigarette smoke and similar observation was found by other worker [13][14] . This observation may suggest effects of cigarettes smoke on the lung could be due to metabolites of cigarette smoke in the lung that can change antioxidant defense system leading to oxidative stress.…”
Section: Discussionmentioning
confidence: 61%